EPEN-23. MOLECULAR HETEROGENEITY AMONG PEDIATRIC POSTERIOR FOSSA EPENDYMOMA. Issue 2 (22nd June 2018) - Pajtler, Kristian W; Wen, Ji; Sill, Martin; Lin, Tong; Hübner, Jens M; Ramaswamy, Vijay; Punchihewa, Chandanamali; Jones, David T W; Witt, Hendrik; Chavez, Lukas; Tatevossian, Ruth G; Grundy, Richard; et al.
Abstract: Previously, we have identified nine distinct molecular groups of ependymoma across all age groups, three in each major anatomical compartment of the CNS: spinal, posterior fossa, and supratentorial. These groups are genetically, epigenetically, transcriptionally, and clinically distinct. The commonest pediatric intracranial ependymomas belong to the posterior fossa type-A (PFA) molecular group. Observing distinct outcomes among children with PFA ependymomas, we tested the hypothesis that further molecular diversity with clinical utility, including possible novel genetic alterations, may exist among these tumors. Genome-wide DNA methylation profiles of 675 pediatric PFA ependymomas were analyzed by unsupervised consensus hierarchical clustering and t-distributed stochastic neighbor embedding. These analyses revealed two major subgroups and nine subtypes of PFA ependymoma. Two major subgroups, PFA-1 and PFA-2, demonstrated distinct gene expression profiles suggesting an independent histogenesis, while nine subtypes were characterized by significant differences in age at diagnosis, gender ratio, pathologic grade, outcome, and frequency of genetic alterations, including chromosome 1q gain and H3 K27M mutations. Specifically, one subtype, PFA-1c, was enriched for 1q gain and had a very poor outcome, while PFA-2c tumors showed an overall survival at 5 years of >90% and elevated levels of OTX2 expression, a potential biomarker for this subtype. We conclude that further molecular refinement of pediatric PFA ependymomas has clinical utility and the potential for enhanced risk assessment or therapeutic stratification. In addition, identification of PFA subgroups and further molecular heterogeneity within these subgroups may help to identify the drivers of PFA ependymomas, which are currently unknown.